ANALISIS SALURAN PEMASARAN AGROINDUSTRI GULA MERAH AREN DI NAGARI TALANG MAUR KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Putri Ayu Lestari P; Farida Hanum Hamzah; Yossie Kharisma Dewi; Vonny Setiaries Johan (SAGU, 2023)
Village Talang Maur is known as an agroindustry producing palm sugar. The agroindustry is experiencing problems in marketing palm sugar which will affect the agroindustry income and has not been able to determine efficient marketing channels. The objective of this study was to examine which marketing channels are the most effective in the palm brown sugar agroindustry. Marketing of palm brown sugar agroindustry consists of two marketing channels, namely channel I includes farmers (producers) – retailers – consumers, channel II includes farmers (producers) – collectors – retailers – consumers. Marketing channel I is an efficient channel consisting of a marketing margin of IDR 4000, 15,6% percentage margin, 84,3% farmer’s share, and 5,27% marketing efficiency while marketing channel II is is an efficient channel consisting of a marketing margin of IDR 8000, 30,5% percentage margin, 71,4% farmer’s share, and 10,01% marketing efficiency Channel I is considered the most efficient due to its low marketing efficiency, high farmer’s share, and lowmarketing margins.